Pericoronary adipose tissue CT attenuation and its association with serum levels of atherosclerosis-relevant inflammatory mediators, coronary calcification and major adverse cardiac events - Göller, Markus; Achenbach, Stephan; Herrmann, Nicolai; Bittner, Daniel O.; Kilian, Tobias; Dey, Damini; Raaz-Schrauder, Dorette; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2021)
Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) derived from coronary CTA might detect coronary inflammation. We investigated a potential association between RCA PCAT attenuation and serum levels of atherosclerosis-relevant cytokines and MACE (coronary revascularization, myocardial infarction and/or cardiac death). Methods: Blood samples of 293 clinically stable individuals (59.0 ​± ​9.8 years, 69% males) were analyzed for atherosclerosis-relevant cytokines including interleukin (IL)-2, IL- 4, IL-6, IL-7, IL-8, IL-10, IL-13, IL-15, IL-17, TNF-a, IP-10, CRP, MCP-1, MIP-1a, Eotaxin and GM-CSF. Subjects also underwent coronary calcium scoring (CCS) followed by CTA. PCAT CT attenuation was measured around the RCA using semi-automated software. Increased RCA PCAT attenuation was defined as PCAT attenuation above the 75th percentile (>−73.5 HU). To assess MACE, 232 individuals were followed for a mean duration of 9.6 ​± ​2.1 years. Results: In patients with increased RCA PCAT attenuation the serum levels of MCP-1 were increased (p ​< ​0.01), whereas levels of anti-inflammatory mediators IL-4 and -13 were significantly reduced (each p ​< ​0.05). Adipocytokine MCP-1 (r ​= ​0.23, p ​< ​0.01) and pro-inflammatory mediator IL-7 (r ​= ​0.12, p ​= ​0.04) showed a mild positive correlation with RCA PCAT attenuation, whereas anti-inflammatory mediators Il-4, -10 and -13 correlated inversely (each r < −0.12, each p ​< ​0.05). 40/232 patients experienced MACE during follow-up. In multivariable Cox regression analysis increased RCA PCAT attenuation was shown to be an independent predictor of MACE (HR 2.01, p ​= ​0.044). Conclusions: Increased RCA PCAT CT attenuation shows a weak association with serum levels of selected atherosclerosis-relevant inflammatory biomarkers. Increased RCA PCAT attenuation is an independent predictor of MACE and may potentially guide future prevention strategies in stable patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Atherosclerosis-relevant inflammatory biomarkers; Coronary calcium score; CT attenuation; Inflammation; MACE; Pericoronary adipose tissue